Dosimetric Evaluation of the QFix kVueTM Calypso Couch Top. (28th April 2021) - Hou, Lingtong; Zhang, Huiqin; Sun, Xiaomei; Liu, Qianqian; Chen, Tingfeng; Liu, Yong; Jiang, Xiaodong; Yao, Shengyu
Purpose: To evaluate the dosimetric accuracy of the default couch model of the QFix kVue TM Calypso couch top in the treatment planning system. Methods: With the gantry 180°, field size 20 × 20 cm, 6 MV, we measured the depth dose, off-axis dose, and dose plane of different depths in the phantom with the couch rails in and out, respectively. Isocenter doses at different angles were also obtained. The results were compared to the doses calculated using the default couch top model and the real scanned couch top model. Then we revised the default model according to the measured results. Results: With "Rails In, " the depth dose, off-axis dose, and dose plane of the default couch top model had a big difference with the dose of the real scanned couch top model and the measured result. The dose of the real scanned couch top model was much closer to the measured result, but in the region of the rail edge, the difference was still significant. With "Rails Out, " there was a minor difference between the measured result, the dose of the default couch top model and the real scanned couch top model. The difference between the measurement and the default couch top model became very small after being revised. Conclusions: It is better to avoid the beam angle passing through the couch rails in treatment plans, or you should revise the parameter of the QFix kVue TM Calypso couch top model based on the measured results, and verify the treatment plan before clinical practice.